The Synergy Between Fintech and Islamic Banking: Expanding Access to Financial Inclusion - Rahmati, Arinal (Al Mashaadir : Jurnal Ilmu Syariah, 2024)
This study aims to examine how the synergy between Fintech and Islamic banking can expand inclusive financial access in Indonesia. Through a literature review, this research identifies the role of Fintech in digital finance based on Islamic principles and the integration of the economic ecosystem. The findings indicate that the synergy between these two sectors holds significant potential for enhancing financial inclusion. However, the study also identifies several challenges, including regulations that have not fully accommodated innovation and the need for improved digital financial literacy. The study concludes that the synergy between Fintech and Islamic banking is a strategic step towards achieving inclusive financial goals in Indonesia, but it requires support from various stakeholders to overcome the existing challenges.